Nuclear analytical methods on ancient Thai rice - K. Won-In (2018)
For more than half of humanity, rice is life. Rice is a grain which has shaped the history, culture, diet and economy of billions of people in Asia. In Thailand, it is the essence of life. Archaeological evidence revealed that rice had been planted in northeastern area of Thailand more than 5,500 years ago which is earlier than in China and India. The ancient rice grains were found in various archaeological sites in Thailand such as Nakhon Nayok, Suphan Buri and Prachin Buri Provinces. In this work, the ancient black rice from Nakhon Nayok Province was elementally analyzed using scanning electron microscope coupled with energy dispersive X-ray fluorescence spectroscopy, proton induced X-ray emission spectroscopy and micro-beam energy dispersive X-ray fluorescence spectroscopy. Infrared (IR) spectroscopy was also used to study the chemical composition and bio-molecular structure. The grains were oblique in shape with a rough surface. Three major elements (Si, Ca and Al) and other trace elements were detected. The IR spectra provided some information about the presence of molecular bonds. © 2013 Akadémiai Kiadó, Budapest, Hungary.